Aplicação da web 2.0 no e-learning: um plugin de fomento à inteligência coletiva para o Moodle - Marins, Paulo Henrique da Silva Alves (2018)
The Web has enabled millions of people to access the Internet and participate in a world filled with change and transformation. Among them are the evolution of the Web itself to Web 2.0 and new possibilities and the development of new educational resources that can be used in distance education or as a support for traditional teaching in what has been called e-learning. Through a literature review, a comparison was made between the evolution of the Web and the evolution of e-learning, which, in the view of many researchers, still needs to evolve in order to take advantage of some of the characteristics of Web 2.0. We also sought to analyze tools and characteristics of Web 2.0, and how they can leverage the construction of knowledge in second generation e-learning platforms. After reviewing the literature, some ways of making e-learning more involving, using principles and characteristics of Web 2.0, have been evidenced, which stimulate students to take a more active stance in the generation and appropriation of knowledge. A plugin for Moodle was developed, inspired by an Amazon.com tool, the customer review. It is believed that its incorporation of this plugin into the e-learning platform contributes to taking it to a new stand, which one could call e-learning 2.0. The first results of experimentation and use of this tool are promising and show that Web 2.0 can contribute more to e-learning, the way it has already contributed to e-commerce over the years.